1969
DOI: 10.12669/pjms.314.7206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of celiac disease in adult type 1 patients with diabetes

Abstract: Objectives:Celiac disease, an autoimmune disease, is related to immune mediated intolerance to gluten. Some studies suggest that Celiac Disease was 20 times more frequent in type 1 patients with diabetes. The objective of our study was to evaluate the prevalence of celiac disease in hospital based type 1 diabetic adults.Methods:Our study was carried out retrospectively in Medeniyet University Goztepe Training and Educational Hospital in Istanbul between 2012–2013. The cohort comprised 482 type 1 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It is reported that celiac disease occurs in 2%-3% of T1DM cases. 20 Celiac disease may lead to suspicion of MODY, as it reduces insulin requirement in some T1DM cases. 21 As far as we can determine, there is no comprehensive study on the association of autoimmune endocrine disorders, including celiac disease, in MODY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that celiac disease occurs in 2%-3% of T1DM cases. 20 Celiac disease may lead to suspicion of MODY, as it reduces insulin requirement in some T1DM cases. 21 As far as we can determine, there is no comprehensive study on the association of autoimmune endocrine disorders, including celiac disease, in MODY.…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting and important findings in our study is the high seropositivity rate (12.5%) for anti‐tTg in children with MODY. It is reported that celiac disease occurs in 2%‐3% of T1DM cases 20 . Celiac disease may lead to suspicion of MODY, as it reduces insulin requirement in some T1DM cases 21 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of definite CD in this study is similar to that reported in T1DM patients from other countries including Turkey (2.3%) and France (1.6%). [22][23][24] Information from sub-Saharan Africa (SSA) is scanty and has been highlighted by Catassi et al, who identified this region as a "black hole" in the world map of CD prevalence, 5 with a call for research in apparently "celiac free" regions such as SSA and the Far-East. 25 Data from North African countries (Egypt, Libya, and Tunisia) report prevalence rates of 4-10.3%, which is similar or even higher than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CD ranges from 2-3% in Finland and Sweden to only 0.2% in Germany [90], and this is similar to the prevalence of CD in the general population of the Asian-Pacific region. The prevalence of CD in diabetes mellitus type 1 (DM1) patients in Western countries has been reported between 1-12% [91], and is quite similar to that in the Asia-Pacific region, which reported a prevalence of CD between 2.3%-11.3% in DM1 patients [33][34][35][36][37][38][39][40][41][42]. The CD prevalence in DM1 patients was significantly higher in children compared to adults (6% vs. 2.5%; P<0.05) in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%